Implementasi Semantic Web Untuk Sistem Penilaian Kelulusan Santri Kelas Akhir Berbasis Ontologi di Ponpes Bintang Sehati - Mulyana, Dadang Iskandar; Azzahra, Salma Latifa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The determination of student graduation at Islamic boarding schools is an essential process that is often still carried out manually and subjectively, potentially leading to inconsistencies between student data and graduation decisions. This study aims to develop a graduation assessment system for final-year students using a Semantic Web approach based on ontology. This method is used to represent knowledge in the form of an ontology that includes graduation indicators such as academic scores, character (akhlaq), discipline, Qur'an memorization and arabic language. This study uses a case study at Ponpes Bintang Sehati, where the system is designed to assist the school in making student graduation decisions more objectively and systematically. Ontology development is carried out using the Protégé application, and inference is performed using a reasoner to determine student graduation status based on the input data. The test results show that the system is capable of assessing the graduation of students in Islamic boarding schools with an accuracy of 88%, producing consistent and accountable evaluations. The system can also be further developed to adapt to various academic and administrative needs within the boarding school environment. This system can also be further developed to be more adaptive to various academic and administrative needs within the boarding school environment